Transfusion Preparedness in the Labor and Delivery Unit: An Initiative to Improve Safety and Cost. Issue 5 (November 2021) - Benson, Ashley E.; Metcalf, Ryan A.; Cail, Kelly; Rollins, Mark D.; Warrick, Christine M.; Falkner, Dane; Clark, Erin A.S.; Nelson, Richard E.; Einerson, Brett D.
Abstract : OBJECTIVE: To evaluate patient safety, resource utilization, and transfusion-related cost after a policy change from universal type and screen to selective type and screen on admission to labor and delivery. METHODS: Between October 2017 and September 2019, we performed a single-center implementation study focusing on risk-based type and screen instead of universal type and screen. Implementation of our policy was October 2018 and compared 1 year preimplementation with 1 year postimplementation. Patients were risk-stratified in alignment with California Maternal Quality Care Collaborative recommendations. Under the new policy, the blood bank holds a blood sample for processing (hold clot) on patients at low- and medium-risk of hemorrhage. Type and screen and crossmatch are obtained on high-risk patients or with a prior positive antibody screen. We collected patient outcomes, safety and cost data, and compliance and resource utilization metrics. Cost included direct costs of transfusion-related testing in the labor and delivery unit during the study period, from a health system perspective. RESULTS: In 1 year postimplementation, there were no differences in emergency-release transfusion events (4 vs 3, P >.99). There were fewer emergency-release red blood cell (RBC) units transfused (9 vs 24, P =.002) and O-negative RBC units transfused (8 vs 18, P =.016) postimplementation compared with preimplementation. Hysterectomies (0.05% vs 0.1%, P =.44) and intensive care unit admissions (0.45% vs 0.51%, P =.43) were not different postimplementation compared with preimplementation. Postimplementation, mean monthly type and screen-related costs (ABO typing, antibody screen, and antibody workup costs) were lower, 9, 753 compared with 20, 676 in the preimplementation year, P <.001. CONCLUSION: Implementation of selective type and screen policy in the labor and delivery unit was associated with projected annual savings of 181, 000 in an institution with 4, 000 deliveries per year, without evidence of increased maternal morbidity. Abstract : A policy of selective type and screen in the labor and delivery unit was associated with cost savings without increased utilization of uncrossmatched blood or increased maternal morbidity.